The Effect of Emotional Intelligence and Work Discipline on Performance with Competence as Intervening Variables in Service Civil Servants Public Works and Spatial Planning for the City of Binjai - Yunita Yunita; Kiki Farida Ferine; Abdi Sugiarto (Lafadz Jaya Publisher, 2023)
This study aims to analyze the Effect of Emotional Intelligence and Work Discipline on Competency Performance as Intervening Variables. This research was conducted at the Public Works and Spatial Planning Office of the City of Binjai. The population in this study was 79 employees using a saturated sample. Data collection was carried out by distributing questionnaires. The data source used is the primary data source. The research model used is path analysis and the measurement tool uses Smart PLS version 3.3.3. The results of this study are Work Discipline has a negative and insignificant effect on Performance, Work Discipline has a positive and significant effect on Competence, Emotional Intelligence has a positive and significant effect on Performance, Emotional Intelligence has a positive and significant effect on Competence, Competence has an insignificant positive effect on Performance, Work Discipline has a positive and insignificant effect on Performance through Competence. Emotional Intelligence has a not significant positive effect on performance through competence.